(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
Ambient Assisted Living technologies offer a unique opportunity to improve the quality of life of persons with mild cognitive impairments while also reducing economic pressures currently experienced by European health systems. Unless an appropriate route to market is found for AAL technologies these benefits will not be realised. This paper highlights the role of Total Cost of Ownership when conducting a technology assessment by reviewing existent literature. In particular, this paper recommends that Total Cost of Ownership tools be developed in conjunction with industry collaboration and that these tools be incorporated as a key award criterion during the assessment and procurement process. This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.